Exploring and Developing Advanced RF MEMS Switches for 5G Applications, Focusing on High Performance Solutions for RF Front End Modules - Gideon, Edikan Nse (Darul Yasin Al Sys, 2025)
This work demonstrates a piezoelectric actuated RF MEMS switch optimized for 5G/6G front end modules, achieving breakthrough performance through novel ruthenium (Ru) contacts and low voltage (4.8V) operation. The switch combines a 150 µm SiN/AlN beam with tapered CPW lines to address critical challenges in mmWave systems: 0.35 dB insertion loss and 32 dB isolation at 28 GHz, outperforming electrostatic MEMS by 60% in voltage requirements and 0.15 dB in loss reduction. Ruthenium contact technology enables >10⁸ cycles at 0.5W with <10% resistance degradation, solving the reliability limitations of conventional gold contacts. Hermetic wafer level packaging with integrated getters yields 92% device survivability after thermal cycling ( 55°C to 125°C). Challenges in 60 GHz isolation (27 dB) and flip chip integration losses (0.1 dB) are quantified, providing clear pathways for 6G scaling. This work establishes a CMOS compatible, high reliability solution for 5G massive MIMO and future reconfigurable THz systems.